Draft Ninth Five Year Plan (1997-2002) Andhra Pradesh Volume-I - Planning Commission (Planning Commission, 1997)
It will be seen that, the increase in the plan expenditure during the third Plan over that of Second Plan was 86.9 percent and the expenditure during the Fourth Plan was 27.4 percent more than that of the Third Plan while there was a quantum jump in the expenditure of the Fifth Plan with 221.8 percent increase from that of fourth plan. The Sixth Plan expenditure was more than double that of the Fifth Plan expenditure was more than that of the sixth plan expenditure by about 85 percent. The Eighth Plan expenditure while the Seventh Plan was also more than double that of the seventh plan expenditure.
Finance and Planning (Plg.Wing) Department, Government of Andhra Pradesh